The Impact of Social Media Usage, QRIS, and Capital on the Income Increase of MSMEs in Johan Pahlawan District, West Aceh Regency - T.M. Riyan; Rollis Juliansyah; Puput Arisna (The Future of Education Journal, 2025)
This study aims to analyze the impact of social media, QRIS, and business capital on the income growth of Micro, Small, and Medium Enterprises (MSMEs) in Johan Pahlawan District, Aceh Barat Regency. Although some MSME entrepreneurs have begun to adopt digital technology, various challenges remain, particularly in the use of social media and the QRIS payment system, especially in Johan Pahlawan District. Data show a decline in the number of MSMEs from 3,042 units in 2020 to 2,500 units in 2024. Additionally, the digital divide, such as low digital literacy and limited business capital, further hinders the optimal development of MSMEs. Therefore, this study aims to further investigate the impact of social media and QRIS use on MSME income in the region, while also formulating strategic recommendations to enhance MSME efficiency and sustainability in adopting digital technology. The research adopts a quantitative approach with a sample of 88 MSME entrepreneurs operating in Johan Pahlawan District. The analytical method used is multiple linear regression. The results show that, partially, social media usage has a positive and significant effect on MSME income growth, QRIS has a positive but not significant effect on MSME income, while business capital has a positive and significant effect on MSME income growth. Simultaneously, social media, QRIS, and business capital significantly and positively influence the income growth of MSMEs in Johan Pahlawan District, Aceh Barat Regency.